2024
DOI: 10.1002/cpdd.1358
|View full text |Cite
|
Sign up to set email alerts
|

Mass Balance and Metabolite Profile after Single and Multiple Oral Doses of Pritelivir in Healthy Subjects

Susanne Bonsmann,
David McCormick,
Jörg Pausch
et al.

Abstract: Pritelivir is a helicase‐primase inhibitor active against HSV. Two human mass balance trials (a multiple‐dose trial and a single‐dose trial) were performed to characterize the absorption, distribution, metabolism, and excretion of 100 mg oral pritelivir combined with a single microdose of 14C‐pritelivir. Blood, urine, and feces samples were collected up to 26 days postdose. The plasma half‐life of pritelivir was 63‐67 hours. Overall, 92% and 66% of the administered dose was recovered in the multiple and single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In previous studies, the extraction of pritelivir from human plasma and urine samples was performed using the protein precipitation method with acidified methanol or acetonitrile (Biswas et al, 2014;Bonsmann et al, 2024;Quenelle et al, 2018). However, given the potential hydrolysis of the sulfamoyl group in sulfonamides (Białk-Bielińska et al, 2012), we decided against using acidic conditions in our method for processing of samples for HPLC analysis.…”
Section: Methods Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the extraction of pritelivir from human plasma and urine samples was performed using the protein precipitation method with acidified methanol or acetonitrile (Biswas et al, 2014;Bonsmann et al, 2024;Quenelle et al, 2018). However, given the potential hydrolysis of the sulfamoyl group in sulfonamides (Białk-Bielińska et al, 2012), we decided against using acidic conditions in our method for processing of samples for HPLC analysis.…”
Section: Methods Developmentmentioning
confidence: 99%
“…To the best of our knowledge, no study has reported a validated method for the quantitative determination of pritelivir in biological matrixes. A brief description of an LC-tandem mass spectrometry method for quantifying pritelivir in biological samples was provided by Quenelle et al (2018), Biswas et al (2014), and Bonsmann et al (2024). Chromatographic separation of the analytes was achieved by Zorbax Eclipse XDB-C 18 or Ascentis RP-Amide HPLC columns.…”
mentioning
confidence: 99%